Impact of intraoperative ventilation parameters on postoperative outcomes in thoracic surgery: a multicenter registry-based analysis - Schnabel, Timon Marvin; Schieren, Mark; Cardenas Artero, Carlos Daniel; Defosse, Jerome; Gerbershagen, Mark Ulrich (Frontiers in Surgery, 2026)
ObjectivesOne-lung ventilation (OLV) is a standard technique during thoracic surgery, yet its impact on postoperative complications and ventilator settings remains under investigation. The objective of this study was to evaluate the impact of intraoperative ventilation parameters on postoperative outcomes in patients undergoing thoracic surgery with OLV.Design and settingA retrospective multicenter cohort analysis was conducted using data from the German Thoracic Registry.ParticipantsThe study encompassed 2,922 patients treated between 2017 and 2021 across eight German centers.InterventionsIntraoperative variables analyzed included driving pressure (DP), positive end-expiratory pressure (PEEP), maximum airway pressure (pMax), tidal volume (TV) per predicted body weight (PBW), and ventilation mode. The primary outcomes of interest were postoperative complications, respiratory complications, and in-hospital mortality.Measurements and main resultsPostoperative complications occurred in 28.7% of cases. Elevated DP (>20 mbar), pMax (>25 mbar), and PEEP (>8 mbar) were significantly associated with increased complication and mortality rates. Patients receiving a TV > 5 mL/kg PBW also showed higher complication rates (p = .003). Respiratory complications occurred in 15.7% of patients and were strongly associated with higher DP, pMax, and OLV duration. Multivariate logistic regression identified OLV > 60 min and pMax >25 mbar as independent predictors of respiratory complications and overall complications.ConclusionIntraoperative ventilation parameters, particularly elevated DP, pMax and PEEP, have been demonstrated to be associated with an increased risk of complications and mortality in patients undergoing thoracic surgery with OLV. These findings lend support to the hypothesis that lung-protective ventilation strategies may improve perioperative outcomes.